CO2 activation through C–N, C–O and C–C bond formation. Issue 3 (18th December 2019) - Eftaiha, Ala'a F.; Qaroush, Abdussalam K.; Okashah, Ibrahim K.; Alsoubani, Fatima; Futter, Jonas; Troll, Carsten; Rieger, Bernhard; Assaf, Khaleel I.
Abstract : CO2 fixation reactions have been explored using different organic substrates upon activation with a superbase. Abstract : A comparative model for the chemisorption of CO2 was explored via three representative reaction pathways: carboxylation of cyclohexanone, carbonation of cyclohexanol, and carbamation of cyclohexylamine. The model substrates were activated using 1, 8-diazabicyclo[5.4.0]undec-7-ene (DBU, an amidine superbase). For each of these reactions, the formation of the corresponding CO2 adducts was confirmed by 13 C nuclear magnetic resonance and Fourier-transform infrared spectroscopy measurements. It was demonstrated that CO2 fixation occurred through either an enol-CO2 adduct ( i.e. carboxylation), proton shuttling process ( i.e. carbonation), or self-activation mechanism ( i.e. carbamation). Volumetric adsorption measurements indicated that cyclohexanol was superior in its uptake capacity (11.7 mmol CO2 g −1 sorbent) in comparison to cyclohexylamine (9.3 mmol CO2 g −1 sorbent) or cyclohexanone (8.5 mmol CO2 g −1 sorbent). As supported by density functional theory calculations, this trend was expected given the fact that the carbonation reaction proceeded through a more thermodynamically favorable reaction process.